CSF-1 and Notch signaling cooperate in macrophage instruction and tissue repair during peripheral limb ischemia - Kapanadze, Tamar; Gamrekelashvili, Jaba; Sablotny, Stefan; Kijas, Dustin; Haller, Hermann; Schmidt-Ott, Kai; Limbourg, Florian P. (Frontiers in Immunology, 2023)
Ischemia causes an inflammatory response featuring monocyte-derived macrophages (MF) involved in angiogenesis and tissue repair. Angiogenesis and ischemic macrophage differentiation are regulated by Notch signaling via Notch ligand Delta-like 1 (Dll1). Colony stimulating factor 1 (CSF-1) is an essential MF lineage factor, but its role in ischemic macrophage development and the interaction with Notch signaling is so far unclear. Using a mouse model of hind limb ischemia with CSF-1 inhibitor studies and Dll1 heterozygous mice we show that CSF-1 is induced in the ischemic niche by a subpopulation of stromal cells expressing podoplanin, which was paralleled by the development of ischemic macrophages. Inhibition of CSF-1 signaling with small molecules or blocking antibodies impaired macrophage differentiation but prolonged the inflammatory response, resulting in impaired perfusion recovery and tissue regeneration. Yet, despite high levels of CSF-1, macrophage maturation and perfusion recovery were impaired in mice with Dll1 haploinsufficiency, while inflammation was exaggerated. In vitro, CSF-1 was not sufficient to induce full MF differentiation from donor monocytes in the absence of recombinant DLL1, while the presence of DLL1 in a dose-dependent manner stimulated MF differentiation in combination with CSF-1. Thus, CSF-1 is an ischemic niche factor that cooperates with Notch signaling in a non-redundant fashion to instruct macrophage cell fate and maturation, which is required for ischemic perfusion recovery and tissue repair.